Testing promotes eyewitness accuracy with a warning: Implications for retrieval enhanced suggestibility. - Thomas, Ayanna K.; Bulevich, John B.; Chan, Jason C.K. (Tufts University. Tisch Library., 2020)
Numerous studies have demonstrated that repeated retrieval boosts later retention. However, recent research has shown that testing can increase eyewitness susceptibility to misleading post-event information (e.g., Chan, Thomas, & Bulevich, 2009) The present study examines the effects of warning on this counterintuitive finding. In two experiments, subjects either took an initial test or performed a filler task after they viewed a video event. They were then given post-event information before they took a final test. Critically, one group of subjects was warned about potential inaccuracies in the post-event narrative and the other group was not. Without a warning, subjects who received an initial test were more likely to endorse misleading post-event information, replicating the retrieval-enhanced suggestibility (RES) effect. However, this RES effect was eliminated when subjects were warned about the veracity of the narrative. These results are consistent with a retrieval fluency account of RES.